Effect of Structure of Carbonized Polymer Dot on the Mechanical and Electrical Properties of Copper Matrix Composites - Jiahui Xu; Wenmin Zhao; Shaoyu Li; Rui Bao; Jianhong Yi; Zhaojie Li (Metals, 2022)
Carbonized polymer dots (CPDs) have been paid a lot of attention by researchers because of their excellent properties due to their unique structure. However, few studies have researched the impact of the CPD structure on composite applications. Herein, CPD and heat-treated CPD (h-CPD) are used to fabricate a reinforced Cu matrix composite. There was a semi-coherent interface between h-CPD and Cu. However, functional groups and polymer chains of CPDs decomposed during heat treatment, weakening the mechanical and electrical properties of the composites. These findings show that CPD structural integrity is vital to composites.